The contribution of auditor individual characteristics to audit quality: an attribution theory approach in a digital context - Oktavia Marpaung; Bertha Elvy Napitupulu; Sita Dewi; Luky Yunia Wennadi; Hadi Santoso (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
The increasing integration of Artificial Intelligence (AI) in the audit process raises concerns about the future role of human auditors. However, human auditors continue to play a critical role in ensuring audit quality through their capability, emotional intelligence, and integrity. This study aims to examine the contribution of these three auditor characteristics in influencing audit quality. Using a quantitative approach, this research collected data from 100 auditors working at public accounting firms (KAP) in the DKI Jakarta region. The sampling technique used was simple random sampling, and data analysis was conducted using multiple linear regression and correlation analysis. The results show that all three variablescapability, emotional intelligence, and integritysignificantly influence audit quality. Among them, capability and emotional intelligence have the strongest positive contribution, followed by integrity. These findings support the attribution theory, which states that individual behavior and outcomes are shaped by internal and external factors. The study contributes to the audit literature by emphasizing the relevance of human factors in an increasingly automated audit environment. Implications include the need for continuous professional development and ethical training to enhance auditors’ competencies in the digital era.